Leveraging business competitiveness by adopting cloud computing in Indonesian creative industries - Fernando, Yudi; Achmad, Syarif; Gui, Anderes (Inderscience Enterprises Ltd., 2019)
The purpose of this study is to identify determinants of the cloud computing adoption in creative industries in Indonesia, and the impact of that adoption on business competitiveness. A theoretical model was developed based on the two complementary models, the technology acceptance model (TAM) and technology-organisation-environment (TOE). An e-survey was conducted among firms that had adopted cloud-computing technology in Indonesia creative industries. This study provides sufficient statistical evidence to infer that perceived usefulness, compatibility, security and privacy, management support and competitive pressure were related to the adoption of cloud computing. Cloud vendors must consider incorporating networks that offer more user friendly and affordable solutions to the market. One factor related user friendliness is that the network must be convenient to use without any issues related to performance. Solutions tied to the cloud should be cost effective for small and medium-sized businesses.